2022
DOI: 10.3389/fgene.2022.897683
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis Reveals Critical Ferroptosis Regulators and FTL Contribute to Cancer Progression in Hepatocellular Carcinoma

Abstract: Background: The carcinogenesis and prognosis of hepatocellular carcinoma (HCC) involve complex molecular mechanisms, and ferroptosis is related to the development and therapeutic efficacy of HCC, but the specific mechanism and prognostic role of ferroptosis-related genes in HCC have not been elucidated.Methods: Differentially expressed gene analysis, Cox regression, and unsupervised consensus clustering were applied to identify crucial ferroptosis regulators and establish ferroptosis-related subtypes in HCC. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
(62 reference statements)
1
5
0
Order By: Relevance
“…Our three subtypes obtained from unsupervised cluster analysis not only exhibited distinct activities in multiple tumor-related pathways but also had critical significance in scores of FAC. Ke et al (57) indicated that FTL could function as a prognostic and diagnostic ferroptosis regulator in hepatocellular carcinoma via random forest analysis, which was consistent with our results that the FTL-dominant cluster possessed a strong connection with ferroptosis. Their resemble conclusion that higher infiltrating immune cells, including Gamma delta T cells and activated CD8+ T cells, emerged in the high FTL expression group, was also confirmed in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Our three subtypes obtained from unsupervised cluster analysis not only exhibited distinct activities in multiple tumor-related pathways but also had critical significance in scores of FAC. Ke et al (57) indicated that FTL could function as a prognostic and diagnostic ferroptosis regulator in hepatocellular carcinoma via random forest analysis, which was consistent with our results that the FTL-dominant cluster possessed a strong connection with ferroptosis. Their resemble conclusion that higher infiltrating immune cells, including Gamma delta T cells and activated CD8+ T cells, emerged in the high FTL expression group, was also confirmed in our study.…”
Section: Discussionsupporting
confidence: 92%
“…We also evaluated for the expression of key genes and proteins associated with ferroptosis, including TFR1 (responsible for the influx of iron inside the cell), FPN1 (efflux transporter of intracellular iron), FSP1 (ferroptosis suppressor protein 1, inhibits ferroptosis by NAD(P)Hdependent reduction of ubiquinone to ubiquinol), FTH (ferritin heavy chain, converts Fe 2+ to Fe 3+ and stores iron to maintain homeostasis), FTL (ferritin light chain, iron reservoir and removes excess iron), and GPX4 (inhibits lipid peroxidation by converting hydroperoxides into lipid alcohols) and the capacity for molecules with anti-ferroptotic activity to prevent key cellular processes implicated in ferroptosis (36,(52)(53)(54)(55)(56). Results of this investigation provide a basis for future mechanistic investigations of ferroptotic cell death and the prevention of disease progression in FECD.…”
Section: Introductionmentioning
confidence: 99%
“…SAT1 and SAT2 regulate polyamine metabolism, a process which has long been implicated in cancer [ 73 , 74 ]. Indeed, higher expression of the FTL ferroptosis regulator, is associated with a poorer prognosis in hepatocellular carcinoma [ 75 ]. Further, expression of the voltage-gated channel VDAC2 is also associated with increased risk in some cancers.…”
Section: Resultsmentioning
confidence: 99%